Much Ado about Nothing: Media Coverage and Citizen Participation in the Debate around the New Communication Law in Ecuador - Ramos, Isabel (2010)
This debate has as its protagonist the media companies that feel attacked not so much by the President’s words as by the government’s desire to regulate activities that, like communication, have been opened up to market logic. Their media campaign has managed to simplify the discussion, turning it into a defense of freedom of speech against “authoritarianism,” the word they use to characterize Correa´s administration. The administration, on the other hand, has not managed to include in this discussion, which affects not only the economic and political interests of the large media emporiums, all citizen groups that, right now, do not feel that the regulatory initiative is their issue. The definitive discussion, to be consistent with rights guaranteed by the Constitution, still has tasks pending.